Sam jeden i inni. A Wrocław Reading of the Works of Józef Mackiewicz, Edited by Małgorzata Misiak, Institute of National Remembrance – Commission for the Prosecution of Crimes against the Polish Nation, Warsaw 2024, pp. 280, ISBN 978-83-8229-974-8 - Davlevič, Mirosław (Slavistica Vilnensis, 2026)
This publication, a collection of studies and polemics by historians, literary scholars, literary theorists, and linguists, expands our understanding of Józef Mackiewicz’s literary and journalistic output and attempts to reinterpret his works from a contemporary perspective. The reviewed publication not only expands our understanding of his literary output but also provokes new questions, further research, and open discourse. Šis leidinys, istorikų, literatūros teoretikų bei lingvistų studijų rinkinys, suteikia naujų įžvalgų apie Józefo Mackiewicziaus literatūrinę ir publicistinę kūrybą. Jame bandoma iš naujo interpretuoti šio rašytojo ir publicisto darbus iš šiuolaikinės perspektyvos. Recenzuojamas leidinys ne tik išplečia mūsų supratimą apie Józefo Mackiewicziaus literatūrinę kūrybą, bet ir skatina kelti naujus klausimus, tolesnius tyrimus ir atvirą diskusiją. Reikšminiai žodžiai: Józef Mackiewicz, literatūrinis ir publicistinis palikimas, istoriniai kontekstai.